Photolysis of Caged-GABA Rapidly Terminates Seizures In Vivo: Concentration and Light Intensity Dependence - Wang, Dan; Yu, Zhixin; Yan, Jiaqing; Xue, Fenqin; Ren, Guoping; Jiang, Chenxi; Wang, Weimin; Piao, Yueshan; Yang, Xiaofeng (Frontiers in Neurology, 2017)
The therapy of focal epilepsy remains unsatisfactory for as many as 25% of patients. The photolysis of caged-aminobutyric acid (caged-GABA) represents a novel and alternative option for the treatment of intractable epilepsy. Our previous experimental results have demonstrated that the use of blue light produced by light emitting diode (LED) to uncage ruthenium-bipyridine-triphenylphosphine-c-aminobutyric acid (RuBi-GABA) can rapidly terminate paroxysmal seizure activity both in vitro and in vivo. However, the optimal concentration of RuBi-GABA, and the intensity of illumination to abort seizures, remains unknown. This study aimed to explore the optimal anti-seizure effects of RuBi-GABA by using implantable fibers to introduce blue light into the neocortex of a 4-aminopyridine (4-AP) induced acute seizure model in rat. We then investigated the effects of different combinations of RuBi-GABA concentrations and light intensity upon seizures. Our results show that the anti-seizure effect of RuBi-GABA has obvious concentration and light intensity dependence. This is the first example of using an implantable device for the photolysis of RuBi-GABA in the therapy of neocortical seizure and an optimal combination of RuBi-GABA concentration and light intensity was explored. These results provide important experimental data for future clinical translational studies.